Residual state ownership, policy stability and financial performance following strategic decisions by privatizing telecoms - Vaaler, Paul M; Schrage, Burkhard N (Journal of International Business Studies, 2009)
We question previous research assuming that privatizing firm performance generally benefits from decreasing state ownership and the passage of time, both of which purportedly align principal–agent incentives promoting organizational decision-making that increases shareholder value. When state ownership shifts from majority and controlling to minority and non-controlling, the performance impact may be positive in the short run, particularly where there is instability in the local investment policy environment. Consistent with this proposition, we develop and test hypotheses derived from a minority and non-controlling or “residual” state ownership framework, grounded in credible privatization and institutional theory. We propose that: (1) residual state ownership positively affects shareholder returns after strategic decisions by privatizing firms because it signals state support for managerial initiatives; (2) the passage of time since initial privatization negatively affects shareholder returns after strategic decisions by privatizing firms because initial undertakings in support of the privatizing firm are reversed; and (3) home-country investment policy stability moderates these two effects – greater stability obviates the need for residual state ownership, and slows policy reversals over time. We find empirical support for our residual state ownership framework in event study analyses of cumulative abnormal returns (“CARs”) associated with 196 major investments announced from 1986 to 2001 by 15 privatizing telecoms from around the world. CARs are positive at 5–25% state ownership levels but turn negative at higher state ownership levels. CARs turn sharply negative within 1–2 years from initial privatization dates. Increasing policy stability diminishes positive ownership and negative time effects on CARs. Results confirm the potential supporting role that residual state ownership can play in enhancing strategic decision-making and financial performance by privatizing firms, particularly where there is instability in the home-country investment policy environment.